Effects of experimental warming on biodiversity depend on ecosystem type and local species composition. Issue 1 (13th September 2016) - Gruner, Daniel S.; Bracken, Matthew E. S.; Berger, Stella A.; Eriksson, Britas Klemens; Gamfeldt, Lars; Matthiessen, Birte; Moorthi, Stefanie; Sommer, Ulrich; Hillebrand, Helmut
Abstract : Climatic warming is a primary driver of change in ecosystems worldwide. Here, we synthesize responses of species richness and evenness from 187 experimental warming studies in a quantitative meta‐analysis. We asked 1) whether effects of warming on diversity were detectable and consistent across terrestrial, freshwater and marine ecosystems, 2) if effects on diversity correlated with intensity, duration, and experimental unit size of temperature change manipulations, and 3) whether these experimental effects on diversity interacted with ecosystem types. Using multilevel mixed linear models and model averaging, we also tested the relative importance of variables that described uncontrolled environmental variation and attributes of experimental units. Overall, experimental warming reduced richness across ecosystems (mean log‐response ratio = –0.091, 95% bootstrapped CI: –0.13, –0.05) representing an 8.9% decline relative to ambient temperature treatments. Richness did not change in response to warming in freshwater systems, but was more strongly negative in terrestrial (–11.8%) and marine (–10.5%) experiments. In contrast, warming impacts on evenness were neutral overall and in aquatic systems, but weakly negative on land (7.6%). Intensity and duration of experimental warming did not explain variation in diversity responses, but negative effects on richness were stronger in smaller experimental units, particularly in marine systems. Model‐averaged parameter estimation confirmed these main effects while accounting for variation in latitude, ambient temperature at the sites of manipulations, venue (field versus lab), community trophic type, and whether experiments were open or closed to colonization. These analyses synthesize extensive experimental evidence showing declines in local richness with increased temperature, particularly in terrestrial and marine communities. However, the more variable effects of warming on evenness were better explained by the random effect of site identity, suggesting that effects on species' relative abundances were contingent on local species composition. Synthesis A global research priority is to understand the consequences of climate change for biodiversity. A growing number of experimental studies have manipulated climatic drivers, in particular changes in temperature, in local communities. In the first quantitative meta‐analysis of community‐level studies across freshwater, marine and terrestrial experiments, species richness declined consistently with experimental warming. This effect was insensitive to warming intensity, duration, and multiple environmental and procedural covariates. However, evenness responses were weakly negative only in terrestrial systems and more variable across ecosystem types. Linear mixed model analyses revealed that the identity of local sites explained nearly 50% of variance in evenness effect sizes, compared to only 10% for richness. This result provides evidence that local species composition strongly constrains changes in relative species abundances in response to warming.